Effect of heat treatment on stainless steel orthodontic wires - Cuoghi, Osmar Aparecido [UNESP]; Kasbergen, Geraldo Francisco; Santos, Paulo Henrique dos [UNESP]; Mendonça, Marcos Rogério de [UNESP]; Tondelli, Pedro Marcelo [UNESP] (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2011)
This study evaluated the effect of heat treatment on CrNi stainless steel orthodontic archwires. Half of forty archwires of each thickness - 0.014 (0.35 mm), 0.016 (0.40 mm), 0.018 (0.45 mm) and 0.020 (0.50 mm) (totalling 160 archwires) - were subjected to heat treatment while the remainder were not. All of the archwires had their individual thickness measured in the anterior and posterior regions using AutoCad 2000 software before and after compressive and tensile strength testing. The data was statistically analysed utilising multivariance ANOVA at a 5% significance level. All archwires without heat treatment that were subjected to tensile strength testing presented with anterior opening, which was more accentuated in the 0.020 archwires. In the posterior region, the opening produced by the tensile force was more accentuated in the archwires without heat treatment. There was greater stability in the thermally treated archwires, especially those subjected to tensile strength testing, which indicates that the heat treatment of orthodontic archwires establishes a favourable and indispensable condition to preserve the intercanine width.
Keywords: Orthodontic Wires; Stainless Steel; Tooth Movement